A critical reading of Hamas and its government since 2006 - Hossain, Ishtiaq; Shobaki, Bilal (Al Zaytouna Centre for Studies and Consultations, 2014)
This chapter is aimed to: 1. Discuss the problems of the Palestinian political system and explain the ways Hamas tried to deal with those problems since elected to power in 2006; 2. Analyse the challenges faced by Hamas, such as that of harmonization between the Islamic ideology of Hamas and democracy and combining resistance with governance. 3. Evaluate Hamas’ political performance since 2006.